C‐reactive protein: An independent predictor for dedifferentiated chondrosarcoma. Issue 10 (24th May 2018) - Nemecek, Elena; Funovics, Philipp Theodor; Hobusch, Gerhard Martin; Lang, Susanna; Willegger, Madeleine; Sevelda, Florian; Brodowicz, Thomas; Stihsen, Christoph; Windhager, Reinhard; Panotopoulos, Joannis
ABSTRACT: Dedifferentiated chondrosarcoma is a rare primary bone malignancy with a very poor prognosis. The aim of the study was to identify pretreatment serum markers as prognostic factors for the overall survival (OS) of patients with dedifferentiated chondrosarcoma. We retrospectively reviewed 33 patients with histologically confirmed dedifferentiated chondrosarcoma treated at our department from 1977 to 2015. Kaplan‐Meier estimation, uni‐ and multivariable Cox proportional hazard model were performed to evaluate the association between serum markers such as the C‐reactive protein and OS. In univariable analysis, CRP was strongly associated with OS (HR 1.35; 95%CI 1.13–1.61; p = 0.001). This association prevailed after adjustment for AJCC tumor stage (HR 1.31; 95%CI 1.02–1.57; p = 0.031) in multivariable analysis. In conclusion, our data gave evidence that baseline CRP is an independent predictor for OS in patients with dedifferentiated chondrosarcoma. CRP could be exploited for the clinical prediction of this disease in the future. © 2018 The Authors. Journal of Orthopaedic Research ® Published by Wiley Periodicals, Inc. on behalf of Orthopaedic Research Society. J Orthop Res 36:2797–2801, 2018. Abstract : We observed a strong association between the C‐reactive protein and OS in patients with dedifferentiated chondrosarcoma (HR 1.35; 95%CI 1.13–1.61; p = 0.001). This association prevailed after adjustment for AJCC tumor stage (HR 1.31; 95%CI 1.02–1.57; p = 0.031) in multivariable analysis. Patients with pre‐operative CRP levels ≥1.0 mg/dl had a lower survival rate than patients with CRP levels <1 mg/dl ( p = 0.026). Our data gave evidence that baseline CRP is an independent predictor for OS in patients with dedifferentiated chondrosarcoma.